Tolerance: the forgotten child of plant resistance - Peterson, Robert K.D.; Varella, Andrea C.; Higley, Leon G. (PeerJ, 2017)
Plant resistance against insect herbivory has greatly focused on antibiosis, whereby the plant has a deleterious effect on the herbivore, and antixenosis, whereby the plant is able to direct the herbivore away from it. Although these two types of resistance may reduce injury and yield loss, they can produce selection pressures on insect herbivores that lead to pest resistance. Tolerance, on the other hand, is a more sustainable pest management strategy because it involves only a plant response and therefore does not cause evolution of resistance in target pest populations. Despite its attractive attributes, tolerance has been poorly studied and understood. In this critical, interpretive review, we discuss tolerance to insect herbivory and the biological and socioeconomic factors that have limited its use in plant resistance and integrated pest management. First, tolerance is difficult to identify, and the mechanisms conferring it are poorly understood. Second, the genetics of tolerance are mostly unknown. Third, several obstacles hinder the establishment of high-throughput phenotyping methods for large-scale screening of tolerance. Fourth, tolerance has received little attention from entomologists because, for most, their primary interest, research training, and funding opportunities are in mechanisms which affect pest biology, not plant biology. Fifth, the efforts of plant resistance are directed at controlling pest populations rather than managing plant stress. We conclude this paper by discussing future research and development activities.
Keywords: Antixenosis; Integrated pest management; Plant breeding; Insect resistance; Antibiosis